Using ChIP-chip technology to reveal common principles of transcriptional repression in normal and cancer cells - Komashko, Vitalina M.; Acevedo, Luis G.; Squazzo, Sharon L.; Iyengar, Sushma S.; Rabinovich, Alina; O’Geen, Henriette; Green, Roland; Farnham, Peggy J. (Genome Research, 2008)
We compared 12 different cell populations, including embryonic stem cells before and during differentiation into embryoid bodies as well as various types of normal and tumor cells to determine if pluripotent versus differentiated cell types use different mechanisms to establish their transcriptome. We first identified genes that were not expressed in the 12 different cell populations and then determined which of them were regulated by histone methylation, DNA methylation, at the step of productive elongation, or by the inability to establish a preinitiation complex. For these experiments, we performed chromatin immunoprecipitation using antibodies to H3me3K27, H3me3K9, 5-methyl-cytosine, and POLR2A. We found that (1) the percentage of low expressed genes bound by POLR2A, H3me3K27, H3me3K9, or 5-methyl-cytosine is similar in all 12 cell types, regardless of differentiation or neoplastic state; (2) a gene is generally repressed by only one mechanism; and (3) distinct classes of genes are repressed by certain mechanisms. We further characterized two transitioning cell populations, 3T3 cells progressing from G0/G1 into S phase and mES cells differentiating into embryoid bodies. We found that the transient regulation through the cell cycle was achieved predominantly by changes in the recruitment of the general transcriptional machinery or by post-POLR2A recruitment mechanisms. In contrast, changes in chromatin silencing were critical for the permanent changes in gene expression in cells undergoing differentiation.